Cash Lotteries in Online Access Panels: Stating the Odds of Winning?. (January 2023) - Gummer, Tobias; Bauer, Irina
Since cash lotteries are frequently employed to stimulate participation in web surveys sampled from online access panels, the present study assesses the research gap concerning the relevance of respondents knowing their odds of winning these cash lotteries. Prior studies on the use of cash lotteries have not provided the odds of winning to respondents, which may have obscured their effects. Based on an experiment in which we varied the number of prizes, the size of prizes, and whether respondents knew the odds of winning, we replicated the findings of prior studies on the use of cash lotteries. Most importantly, our findings show that knowing the odds of winning cash lotteries did not affect the participation in our survey and did not influence the effects of other survey design elements. In our study, we provide survey practitioners with recommendations on the use of cash lotteries in online access panels and close with an outlook for future research on this topic.